2018
DOI: 10.5194/angeo-36-1471-2018
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the 630.0 nm airglow emission with meridional neutral wind and neutral temperature around midnight

Abstract: Abstract. The ISUAL payload onboard the FORMOSAT-2 satellite has often observed airglow bright spots around midnight at equatorial latitudes. Such features had been suggested as the signature of the thermospheric midnight temperature maximum (MTM) effect, which was associated with temperature and meridional neutral winds. This study investigates the influence of neutral temperature and meridional neutral wind on the volume emission rates of the 630.0 nm nightglow. We utilize the SAMI2 model to simulate the cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Thus, it is important for data to correctly indicate the locations with the largest emission rates, so as not to misguide the development of theories. For the 630.0-nm airglow, calculations of the volume emission rates by Chiang et al (2018) have shown that the presence of neutral wind could significantly shift the latitudes and heights of airglow occurrence. Unfortunately, as we have discussed, radiance data-with the line-of-sight measurements projected to the tangent point as in the case of ISUAL-could underestimate the height of the brightest region in a 630.0-nm airglow event by 15 km or more.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is important for data to correctly indicate the locations with the largest emission rates, so as not to misguide the development of theories. For the 630.0-nm airglow, calculations of the volume emission rates by Chiang et al (2018) have shown that the presence of neutral wind could significantly shift the latitudes and heights of airglow occurrence. Unfortunately, as we have discussed, radiance data-with the line-of-sight measurements projected to the tangent point as in the case of ISUAL-could underestimate the height of the brightest region in a 630.0-nm airglow event by 15 km or more.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these reactions, the volume emission rate of the OI 630.0-nm airglow, according to Chiang et al (2018), is…”
Section: Reconstruction Of Airglow Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…where O( 1 D) is an excited state of atomic oxygen responsible to emit a photon of 630.0 nm. The emission rate, therefore, depends on the concentration of the electron density [e] and its height profile (Chiang et al, 2018). The electron density profile, especially its bottom side profile, could be estimated by ionograms.…”
Section: Possible Direct Influence Of Primary Wave In the Ionospherementioning
confidence: 99%
“…On the other hand, the ionosonde at Cachoeira Paulista observed the peak altitude at 260 ± 10 km. From the estimated electron density profiles, we calculated the OI 630 nm volume emission rates based on the equation presented by Chiang et al (2018). The peak emission altitude at Fortaleza was at 200 km.…”
Section: Possible Direct Influence Of Primary Wave In the Ionospherementioning
confidence: 99%